A microfluidics-derived growth factor gradient in a scaffold regulates stem cell activities for tendon-to-bone interface healing. (27th May 2020) - Lyu, Jingtong; Chen, Long; Zhang, Jiqiang; Kang, Xia; Wang, Yunjiao; Wu, Wenjie; Tang, Hong; Wu, Jun; He, Zhiyu; Tang, Kanglai
Abstract : Treatment of tendon-to-bone interface injury has long been challenging in sports medicine. Abstract : Treatment of tendon-to-bone interface injury has long been challenging in sports medicine. The major obstacle lies with the complicated three-layer structure of the tissue that consists of a bone region with osteocytes, a tendon region with tenocytes and a transitional region with chondrocytes. Conventional tissue engineering approaches using simply biomaterial scaffolds, stem cells and combinations of them had limited abilities to reconstruct the gradient structure with normal biomechanical properties. We herein aim to construct a three-layer structure with bone marrow-derived stem cells and tendon stem cells cultured in a decellularized tendon scaffold, through application of a gradient of biological cues in the longitudinal direction of the scaffold that guides the stem cells to differentiate and remodel the extracellular matrix in response to different medium concentrations in different regions. A microfluidic chip, on which a tree-like flow pattern was implemented, was adopted to create the concentration gradient in a dichotomous manner. We screened for an optimized seeding ratio between the two stem cell types before incubation of the scaffold in the medium concentration gradient and surgical implantation. Histology and immunohistochemistry assessments, both qualitatively and semi-quantitatively, showed that the microfluidic system provided desired guidance to the seeded stem cells that the healing at 8-week post-implantation presented a similar structure to that of a normal tendon-to-bone interface, which was outstanding compared to treatments without gradient guidance, stem cells or scaffolds where chaotic and fibrotic structures were obtained. This strategy offers a potentially translational tissue engineering approach for better outcomes in tendon-to-bone healing.